Pengaruh Model Pembelajaran Kooperatif Tipe Think Pair Share dan Tipe Two Stay Two Stray terhadap Hasil Belajar Bahasa Indonesia Siswa Kelas X SMA Negeri 1 Angkola Barat Kabupaten Tapanuli Selatan - Hasian Romadon Tanjung; Syahrul R; Harris Effendi Thahar (Fakultas Bahasa dan Seni UNP, 2013)
Abstract: This research was based on the low Tenth Students’ Indonesian result studying of SMA Negeri 1 Angkola Barat Kabupaten Tapanuli Selatan. The purpose of this research, first, explain the students’ result studying of Indonesian that uses cooperative learning think pair share type is higher than two stay two stray type. Second, explain the interaction between cooperative learning think pair share type and two stay two stray type that is applied based on basic competence to influence the result studying of Indonesian. Third, explain the result studying of Indonesian lesson of students that have high competence by using cooperative learning think pair share type is more than the students that have high competence by using cooperative learning two stay two stray type. Fourth, explain the result studying of Indonesian lesson of students that have low competence by using cooperative learning think pair share type is more than the students that have low competence by using cooperative learning two stay two stray type. This research is using experiment method by factorial 2x2 design. This population is about 142 students, Consist of 4 classes from tenth grade of SMA Negeri 1 Angkola Barat Kabupaten Tapanuli Selatan. The samples of this research are X1 and X3 grade that is specified trough purposive sampling technic. Before doing act, the basic competence of students are tested to know the difference of the students’ ability. How to get the students’ result of Indonesian studying by using a test which is used before to get the validity and reliability level. From 45 items tested, it gets 30 decent items. The first, third and fourth hypothesis are tested by Average of two trials (t-test) and the second hypothesis is tested by Anova test two paths (f-test). Before the average two trial is used, requirement analysis date is done first, it is normality test with Lilliefors and Homogenity of variance test. The result of the first hypothesis test shows that it gets th = 3,78 > tt = 1,67 based on t-test at real level 0.05, it means H1 received and H0 rejected. Second, based on F-test at real level 0.05, it gets 0,79 < 4,17 means Fcount < Ftable, it means H1 rejected and H0 received. Third, based on t-test at real level 0.05 gets th = 4,228 > tt = 1,73 it means H1 received dan H0 rejected. Fourth, based on t-test at real level 0.05 gets th = 1,851> tt = 1,73 it means H1 received dan H0 rejected. Thus, it can conclude that the students’ Indonesian result studying by using the cooperative learning think pair share type is higher than the students’ Indonesian result studying by using the cooperative learning two stay two stray type of the X grade of SMA Negeri 1 Angkola Barat Kabupaten Tapanuli Selatan at 5% significant level. Keyword: model pembelajaran kooperatif, think pair share, two stay two stray, kemampuan awal, hasil belajar.